2021
DOI: 10.3389/fimmu.2021.652054
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Advances in Locally Advanced and Recurrent/Metastatic Head and Neck Squamous Cell Carcinoma and Its Relationship With Human Papillomavirus

Abstract: Head and neck cancer (HNC) is the sixth most common malignancy worldwide; head and neck squamous cell carcinoma (HNSCC) account for the most cases of HNC. Past smoking and alcohol consumption are common risk factors of HNSCC; however, an increasing number of cases associated with human papillomavirus (HPV) infection have been reported in recent years. The treatment of HNSCC is integrated and multimodal including traditional surgery, radiotherapy, chemotherapy, and targeted therapy. Since pembrolizumab was appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“… 16 Whereas single clinical trials found a better outcome of HPV positive tumors during immune checkpoint inhibition, a recent meta-analysis was negative. 44 45 In the CheckRad-CD8 trial these patients had an excellent prognosis with a 2-year PFS rate of 94% in the RIT cohort. However, it has to be considered that these patients also have a very good prognosis on platinum-based radiochemotherapy as demonstrated in the RTOG 1016 trial.…”
Section: Discussionmentioning
confidence: 98%
“… 16 Whereas single clinical trials found a better outcome of HPV positive tumors during immune checkpoint inhibition, a recent meta-analysis was negative. 44 45 In the CheckRad-CD8 trial these patients had an excellent prognosis with a 2-year PFS rate of 94% in the RIT cohort. However, it has to be considered that these patients also have a very good prognosis on platinum-based radiochemotherapy as demonstrated in the RTOG 1016 trial.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment of recurrent and/or metastatic OPSCC is similar to that of other recurrent and/or metastatic HNSCC. There is no specific recommendation for oropharyngeal tumors and no particularities according to the HPV status [8,44,90]. However, even with a metastatic disease, HPV-positive OPSCC patients still harbor a better prognosis than HPV-negative OPSCC patients [90,91].…”
Section: Recurrent And/or Metastatic Opsccmentioning
confidence: 99%
“…ICIs are the blocking antibodies against inhibitory immune checkpoints (ICs) targeting the specific mechanisms that tumor cells employ to evade immune system detection [ 8 ]. Despite the promising results of ICIs therapy in melanoma [ 9 , 10 ], urothelial carcinoma [ 11 ], lung tumors [ 12 , 13 ], colorectal tumors [ 14 ], and head and neck squamous cell carcinoma [ 15 ], clinical gains are far from universal. In some of the major tumor types (e.g., breast and pancreas), the clinical efficacy of ICIs remains very limited [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%